The process of thicket encroachment in semi-arid savanna: community patterns and biotic interactions - Nell, Rhys (Rhodes University, Faculty of Science, Botany Department)
Bush encroachment in savannas is widespread in South Africa and is concerning, from both socio-economic and conservation viewpoints, as it affects ecosystem services, functioning and productivity. This phenomenon depends on multiple factors such as history, vegetation, management and environmental conditions, and their interplay. Encroachment into savannas has been relatively well-documented, however understanding of the different roles of tree-tree interactions between species that occur during this process is still limited. This includes the interactions causing spatial patterning, or how interactions and outcomes change over time in terms of encroachment succession from open savanna to closed-canopy thicket. The main objectives of this research are to document thicket establishment in a savanna ecosystem and consider the ecological roles of the key woody species and the abiotic properties of their micro-sites. Determining interactive effects of species co-occurrence is critical to understanding or predicting patterns and changes in biodiversity, nutrient distribution and available water resources. It is also imperative in determining correct and effective land management practices, particularly for reducing bush encroachment and its negative effect on rangelands. All data were collected on Endwell farm, located in the Smaldeel region of the Eastern Cape, South Africa. Endwell farm is a semi-arid savanna with a mean annual rainfall of 730 mm. First, I examine and describe the thicket encroachment process by exploring the associations between species and their size classes in the field. This was done by using plot-based belt transects and looking at changes in species size-class compositions from early to late successional stages. Association rules (market basket) analysis was used to identify the most common species size-class association patterns. The association between the savanna tree Vachellia karroo and the thicket pioneer Scutia myrtina was the most prevalent at all stages, with V. karroo being central to all associations in the first stage of encroachment; during later stages of encroachment, associations shift to incorporating other thicket pioneer species. The demography and clump formation of S. myrtina was strongly linked to associations with V. karroo to initiate bush clump formation. Results suggest that mature V. karroo facilitate the establishment and growth of S. myrtina. These two species were the focus of more detailed investigations to explore the nature and magnitude of their interspecific interactions. I then examined the effects of pairwise tree interactions between V. karroo and S. myrtina on soil and leaf nutrient content. I measureddifferences betweeninter-canopy and sub-canopy soil nutrient content, and the effect of associations on plant leaf nutrients, between pair-size combinations and individual controls. Results confirmed that pair-size tree interactions affected both soil nutrient and leaf nutrient content. All individuals increased soil K, N and organic C in the sub-canopy, while association with V. karrooincreased S. myrtinafoliar N, Pand K. In contrast, association with S. myrtinaloweredV. karroofoliar N, P and K. Small S. myrtina individuals werefound to benefit most from establishing and growing next to a large V. karroo individual, through mechanisms affecting soil and foliar nutrients. Scutia myrtina individuals establishing in association with smaller size classes of V. karroo showed no significant effects. I tested for positive and negative effects of pairwise tree interactions between Vachellia karroo and Scutia myrtina on available soil water and plant water potential (Î¨). This was done by looking at differences betweeninter-canopy and sub-canopy soil moisture and bulk density and associations on plant water stress (pre-dawn and mid-day leaf Î¨), between pair-size combinations and individual controls. I also selectively removed large V. karroo individuals from pairs to confirm the effects of competition andfacilitation. Similar to other studies, results confirmed positive and negative effects of pairwise tree interactions. Small S. myrtina individuals weremost facilitated by establishing and growing up next to a large V. karroo individual, through mechanisms affecting soil water content, bulk density and leaf Î¨. Scutia myrtina establishing in association with other size classes of V. karroo were much less facilitated, showing no significant effects. In contrast, large S. myrtina showed competitive interactions with V. karroo.
Keywords: Scrub encroachment; Savanna ecology; Biotic interaction; Plant nutrients; Plant-water relationships